Diplomasi Budaya Jepang dan Korea Selatan di Indonesia tahun 2020: Studi Komparasi - Annisa Nur Islamiyah; Nafila Maulina Priyanto; Ni Putu Dyana Prabhandari (Universitas Airlangga, 2020)
Products of the creative industry, which falls under the category of culturalproducts, represent one of soft power instruments capable of influencingpolicy-making processes. Japan and South Korea are two states that haveimplemented internationalization strategies on their creative industryproducts in order to boost economy. In addition to becoming sectors thatcontribute to the economy, by the means of the Korean Hallyu and CoolJapan, the creative industries of Japan and South Korea have becomeinstruments of cultural diplomacy aimed at influencing public opinionson both states. In Indonesia, differences in the development strategiesimplemented by both states have influenced the degree of success in theircultural diplomacy. This research aims to identify differences betweenthe strategies implemented by Japan and South Korea in conductingcultural diplomacy in Indonesia. This research has found that the culturaldiplomacy conducted by Japan has been less successful due to the lackof incorporation of cultural values in its internationalization strategy, aswell as the lack of government support for its creative industry.